If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X2-11X-26=0
We add all the numbers together, and all the variables
X^2-11X-26=0
a = 1; b = -11; c = -26;
Δ = b2-4ac
Δ = -112-4·1·(-26)
Δ = 225
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{225}=15$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-15}{2*1}=\frac{-4}{2} =-2 $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+15}{2*1}=\frac{26}{2} =13 $
| 2k+6k=0 | | 5t=(-7.5) | | 11d^2-49d=0 | | 5x+7=9x−1 | | 2(x^2+3)=30 | | (-64)+6x=146-8x | | Z^2+36z=0 | | 1/2x^2+x+35/2=0 | | 5x-3{x-5}=13 | | 12u+10+14=80 | | 40=20x+20 | | -4*(-x+10)=(4x+60)/2 | | 2•0-3f=24 | | -21(-5x+14)=-440 | | -6x+-3=6x-1 | | 8n+(4n+5)=3 | | 2(3)-3f=24 | | 5x-15=2.x+15 | | X+x+13+x+38=180 | | 2×+3=6-x | | 2(10+-1y)+2y=20 | | 0.04x-0.07=0.03x | | -13+2x+x-3=5 | | 7+x=88 | | -30-2a=-4(a+6) | | (5x^2+x)(5x^2+x)(x-11)=0 | | -3x-6x=16-8x-3x | | 6x-13+13+9x+27=3x+74 | | 27^2x=(1/9)^(x-3) | | -8-6x=-6x+x | | n+32.48=20 | | 6p+3=5p-3 |